Italijanščina kot tuji jezik na področju gostinsko-turistične stroke - Ukmar, Amina (Vestnik za tuje jezike, 2017)
The article analyses the linguistic content and typology of exercises or activities designed to develop students' (verbal) communication skills in the available textbooks for Hospitality and Tourism published in Slovenia in the recent years. The presented research aimed at establishing to what extent and with the help of what type of exercises and activities a student can develop oral communication and, in particular, to analyse the content of these exercises. The study is focused on the presence of authentic materials and tasks intended for practicing productive and receptive skills in the selected textbooks as well as on the extent to which the professional terminology is integrated in the interpretation together with the examples. Last but not least, focus is placed on the consolidation of the most important grammatical structures. Of special interest, therefore, is the extent to which the student is guided and prepared for independent communication in various professional situations with the help of textbook exercises. The study revealed that the analysed learning material is mainly based on the communicative approach and that the students are encouraged to use oral expression. However, the share of exercises with which the students practice using the communicative patterns and language structures in the context of catering and tourism is too low. Our proposal is, therefore, that the teaching content should focus more on the communicative situations in which the professionals of tourism and hospitality find themselves, and should not primarily be oriented towards the guests or the users of tourism and hospitality services. In addition, the textbooks should contain more authentic material, since this is the best starting point for learning, understanding, and practising independent use of key professional terminology. Furthermore, even the grammatical exercises mostly include general language rather than the language and content that is intrinsically linked with catering and tourism.
Keywords: Italian; italijanščina; foreign languages; tuji jeziki; jezik stroke; language for specific purposes; catering and tourism; gostinstvo in turizem; učna gradiva; textbooks; govorno sporazumevanje; oral communication; authentic materials; avtentična gradiva; exercices; naloge; task types; tipologija nalog